Peningkatan Kesehatan Lansia Melalui Pendampingan Kegiatan Lansia Sehat: Improving Elderly Health Through Assistance with Healthy Elderly Activities - Kusumaningrum, Puput Risti (Chakra Brahmanda Lentera Institute, 2023)
Elderly is part of the life process that cannot be avoided and will be experienced by every human being. At this stage humans experience many changes both physically and mentally, where there is a setback in the various functions and abilities they once had. Elderly is someone who has reached the age of 60 years and over. This activity aims to improve the health of the elderly through mentoring healthy elderly activities. The method used in the activity is pre-post test without a control group. The sampling technique with a total sampling of 30 samples. The instruments used were questionnaires on the level of knowledge of hypertension and observations using a sphygmomanometer. The results of the community service showed that prior to conducting health counseling, 16 (53%) respondents had insufficient knowledge, 8 (27%) respondents were sufficient, and 6 (20%) respondents were good. After being given health counseling, the level of knowledge of the respondents became less knowledge by 2 (7%) of respondents, enough by 5 (16%) of respondents, and good by 23 (77%) of respondents. In conclusion, after counseling, it can be seen that the respondent's knowledge has increased and this method is considered effective in increasing the respondent's knowledge.